Characterization of metallic electrical contacts to SnO2 thin films lightly doped with Eu3+ ions, and photo-induced resistivity - da Silva, Vitor D. L. [UNESP]; de Andrade, Aloisio [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Floriano, Emerson A. [UNESP]; Maciel, Jorge L. B. [UNESP]; Ravaro, Leandro P. [UNESP]; Santos, Julio C. [UNESP] (Elsevier B.V. Sa, 2012)
Lightly Eu3+-doped (0.05%) SnO2 thin films are deposited by the sol-gel-dip-coating technique, topped by alternative metallic layers of Al, Sn or In, arranged in a parallel layout on the thin film surface, and deposited by the resistive evaporation technique. Electrical characterization results show that the sort of deposited metal strongly modifies the device resistance, besides thermally treated metallic layers decreases the device resistivity, which may be associated with increased tunneling probability. Current as function of applied voltage show a good linear symmetry contacts for a large temperature range (30-320 K). However, this feature is due to the MSM (metal-semiconductor-metal) structure of the device, because the conduction through the reversed-biased junction is the main mechanism of electrical transport at Schottky potential barriers. The barrier height evaluation is also presented, considering that the dominant mechanism is the thermionic emission through the reversed-biased junction, yielding values in the range 124 meV for annealed In contacts to 187 meV for untreated Sn contacts. This paper also shows results of photo-induced electrical characteristics under irradiation with below bandgap (450 nm) as well as above bandgap (266 nm) light on the SnO2 thin films, where the surface is coupled with untreated Sn contacts. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Interfaces; Thin films; Sol-gel growth; Electrical properties